MySQL Database Development Mastery - Williams, Trevoir (Packt Publishing, 2020)
Explore the fundamentals and best practices of MySQL Server and MySQL Workbench by building real-time databases About This Video Discover how to create and manage databases in MySQL Server and MySQL Workbench Gain a comprehensive understanding of SQL queries, statements, and structures Build a small school management database to understand the development principles of a database In Detail MySQL is a database that is used by the biggest social media platforms, such as Facebook, Twitter, and YouTube. Thanks to its performance, reliability, and ease-of-use, MySQL has become one of the most popular open-source databases. This course will help you get to grips with the fundamentals of the two most powerful MySQL assets-MySQL Server and MySQL Workbench-for effectively designing and maintaining databases. The course begins with an introduction to MySQL Server and its databases and demonstrates the process of installing MySQL Server and MySQL Workbench on your machine. Once the setup is complete, you'll explore the concepts of manipulating data and tables with MySQL queries. Moving on, you will discover how to connect, create, and remove a database; how to insert data into the table using SQL scripts and Workbench; how to select, update, and delete data in the table; along with learning some CRUD operations. As you progress, you'll understand the importance of relationships, foreign keys, and normalization in MySQL. Finally, you will delve into aggregate functions, such as AVG, COUNT, MIN, and MAX, and find out how to perform calculations on a set of values and return a single value. By the end of this course, you'll have gained the basic MySQL Server and MySQL Workbench skills needed to design and maintain databases.
Keywords: Electronic videos